A study effect of electronic learning system on employee commitment at Petronas Dagangan Berhad / Amirul Hafiz Othman - Othman, Amirul Hafiz (Faculty of Business and Management, 2018)
E-learning has become the popular learning approach that has been utilized by many organization and society in this recent year. E-learning can be refer to the use of technological devices such as computer, internet, and other that can be used to deliver the information and gives instruction. Many institutions have recognized that e-learning has benefits in allowing the user get access to the system diversely without any geographical boundaries. E –learning also has benefits in term of cost effective, on the spot training, lesser cost which will lead to the success of the organization. Meanwhile, employee commitment has become the sources of competitive advantage for many organizations and thus employee commitment can be defined as the trust in the relationship that has been build and the effort as to retain the relationship. Employee commitments will drives them into achieving the goals which they wanted. Therefore, the study is identifying the relationship between effect of e-learning system and employee commitment. This study is conducted at PETRONAS Dagangan Berhad. This research is quantitative research as the use of questionnaire has taken place in this research. Sample selection is probability sampling in which is simple random sampling. There will be 212 PETRONAS Dagangan Berhad employees will be involved in giving information for this study. For statistical analysis of questionnaire, we are using Statistical Package for Social Science (SPSS) Version 20 Software. Several tests such as reliability test, descriptive statistic, frequency analysis, Pearson’s correlation and multiple regression analysis are chosen to analyse the data. Dependent variable of this study is employee commitment. Meanwhile, the independent variable consists in this research are learners satisfaction, personalize learning, 24/7 access to training material and efficiency.